Effectiveness of Fluorescent Viability Assays in Studies of Arctic Cold Seep Foraminifera - Melaniuk, Katarzyna (Frontiers in Marine Science, 2021)
Highly negative δ13C values in fossil foraminifera from methane cold seeps have been proposed to reflect episodes of methane release from gas hydrate dissociation or free gas reservoirs triggered by climatic changes in the past. Because most studies on live foraminifera are based on the presence of Rose Bengal staining, that colors the cytoplasm of both live and recently dead individuals it remains unclear if, and to what extent live foraminifera incorporate methane-derived carbon during biomineralization, or whether the isotopic signature is mostly affected by authigenic overgrowth. In this paper, modern foraminiferal assemblages from a gas hydrate province Vestnesa Ridge (∼1,200 m water depth, northeastern Fram Strait) and from Storfjordrenna (∼400 m water depth in the western Barents Sea) is presented. By using the fluorescent viability assays CellTrackerTM Green (CTG) CMFDA and CellHunt Green (CHG) together with conventional Rose Bengal, it was possible to examine live and recently dead foraminifera separately. Metabolically active foraminifera were shown to inhabit methane-enriched sediments at both investigated locations. The benthic foraminiferal faunas were dominated by common Arctic species such as Melonis barleeanus, Cassidulina neoteretis, and Nonionellina labradorica. The combined usage of the fluorescence probe and Rose Bengal revealed only minor shifts in species compositions and differences in ratios between live and recently dead foraminifera from Storfjordrenna. There was no clear evidence that methane significantly affected the δ13C signature of the calcite of living specimens.